Cash McCall [videorecording (DVD)] - Pevney, Joseph; Garner, James. 1928-2014; Wood, Natalie; Foch, Nina; Jagger, Dean, 1903-1991; Marshall, E. G., 1914-1998; Hawley, Cameron, 1905-1969 (Distributed by Warner Home Video, 2009)
Cash McCall is a young and slick business man who is enjoying himself plenty of late. He buys failing businesses and resells them. Grant Austen's Plastics is just said business. This is even more of a prize to Cash, for Cash is also making a bid for Austen's beautiful daughter, Lory. This is Cash's toughest deal ever.